The Principles of Advocacy Organization and Its Activities - ALEYNIKOV, Boris; ALEYNIKOVА, Anastasia (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017DO - 10.14505//jarle.v8.7(29).01, 2017)
The article gives a scientific study of the principles of advocacy. Formulated the concept and classification of principles of advocacy. On the basis of the sphere of dissemination of the principles of advocacy classified into fundamental principles (independence, professional competence, confidentiality, avoiding conflict of interest), organizational principles (territoriality, dependence of the judicial system, specialization, corporate governance, availability) and principles (efficiency, multidisciplinary approach, differentiated remuneration).